Murder on the Orient Express - Christie, Agatha, 1890-1976.; Sachs, Andrew (Los Angeles : Audio Renaissance, 2001)
The dapper detective Hercule Poirot, for whom murder-solving is a precise, intellectual exercise, agrees to interview all aboard the famous train's Calais coach, hoping to find the killer of an American millionaire before the local police arrive.
Abridged.
In container (18 cm.).
Read by Andrew Sachs.
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Orient Express (Express train) -- Fiction